Is sustainable tourism development important for an emerging economy? A study in Malaysia on factors affecting locals’ attitude - Teo, Poh-Chuin (RMP Publications, 2023)
The tourism industry has been recognized as one of the most contributing industries to many countries in the world. However, the COVID-19 pandemic has badly hit the tourism industry, which has deteriorated its performance since 2019. Many countries are moving toward the endemic phase, including Malaysia, and they are opening the country border again to the global travelers. This study aims to examine the attitude of Malaysians toward the country’s tourism development, whereby the influence of perceived sustainable local community development, specifically on economic impact, social impact, and environmental impact, was examined. Based on data collected from a total of 210 survey responses using purposive sampling, economic impact and environmental impact have shown significant positive influence on the attitude of the locals. Implications to policy makers, researchers and market practitioners have also discussed in this study. This paper ends with discussion on research limitations and recommendations for future researchers.